Sprechkompetenz im DaF-Unterricht an slowenischen Gymnasien - Retelj, Andreja (Vestnik za tuje jezike, 2016)
This article presents the speaking competence in German language classes in Slovenian secondary schools from three different perspectives: it gives the definition of speaking competence within the Common European Framework of Reference for Languages (CEFR), within the Syllabus for German for Secondary Schools, and within learning activities for teaching and developing speaking competence in German foreign language classes. The analysis of both documents shows that great importance is attributed to speaking competence, but, at the same time, both documents provide us with guidelines in terms of what is expected from each student at a certain CEFR level and what kind of language competence and knowledge a student is required to demonstrate in order to qualify for a certain level. The syllabus additionally adapts CEFR guidelines to the learning context and target groups. It is thus expected of a Slovenian secondary school student to be able to communicate on an independent user level at the end of the secondary school education. Both documents define speaking competence theoretically. However, the documents do not provide insight into the development of speaking competence in particular classes. The analysis of the survey conducted among teachers showed that speaking competence is developed only within limited frameworks. The most frequent reasons were lack of time, difficult error correction, insufficient classroom control, poor students' performance, lack of motivation and large classes. The survey also revealed that teachers chose only a small repertoire of learning activities for developing speaking competence. In order for Slovenian secondary students to truly develop high-level speaking competence, teachers should considerably alter their views on their own role, as well as a student's role in the classroom, introduce learning activities into language classes which develop free speech, and above all encourage students' independence and responsibility for their own learning process.
Keywords: nemščina kot drugi jezik; didactic method; didaktika; srednješolsko izobraževanje; Slovenia; Slovenija; govorna zmožnost; učne dejavnosti; izobraževalni programi; SEJO